Three Policy Issues in Deciding the Cost of Nursing Home Care: Provincial Differences and How They Influence Elderly Couples' Experiences - Robin L. Stadnyk (Law & Governance, 2009)
[This article was originally published in Healthcare Papers, Volume 9, Number 4.] Nursing home care is subsidized in all Canadian provinces, but residents must personally contribute to the cost. This paper explores policy issues that have led to differences in costs of nursing home care among provinces, and how policy and cost differences influence the experiences of married couples when one spouse requires nursing home care. The paper is based on a multiple-case study of three Canadian provinces, each of which had a different system for determining personal contributions to the cost of care. Cross-case analysis of payment systems showed that provinces addressed three main policy issues in determining the cost of care: (a) what costs should be the responsibility of nursing home residents, (b) how subsidies should be determined and (c) how community-dwelling spouses of nursing home residents should be assured of an adequate income. In provinces with policies that resulted in higher care costs to couples and lower amounts of income and assets available to the community-dwelling spouses, study participants described reduced discretionary spending, increased financial concerns and perceptions of system unfairness. This paper discusses the implications of these three policy issues and recent related changes to provincial policies.
Keywords: nursing home, healthcare host, chronic care